Penggunaan Abu Marmer Dan Fly Ash Sebagai Pengganti Sebagian Semen Pada Beton Normal - George Andre Papendang; Jonie Tanijaya; Olan Jujun Sanggaria (Paulus Civil Engineering Journal, 2023)
Every year the amount of waste continues to increase, one of which is marble ash waste, the amount of waste will continue to increase both in the construction, extractive, facilitative and other industries. The purpose of this study was to determine the compressive strength, split tensile strength and modulus of elasticity with research conducted at the Laboratory of Structures and Materials at the Christian University of Indonesia Paulus Makassar. The test object used is a cylinder with a diameter of 150mm and a height of 300mm. The results of the compressive strength test with the addition of 0% marble ash with 10% fly ash increased by 4.930% from the addition of 8% marble ash with 10% fly ash which experienced an increase of 1.533%. However, in the addition of 12% marble ash with 10% fly ash, there was a decrease of 9.035% from the design compressive strength value of 25 MPa. The split tensile strength test results (ft) obtained split tensile strength values ​​of 2,713 MPa, 2,642 MPa and 2,477 MPa. For the results of the Elasticity Modulus (E) test, the value obtained by adding 0% marble ash with 10% fly ash, 8% marble ash with 10% fly ash and 12% marble ash with 10% fly ash, is 7979.762 MPa, 7597, 352 MPa and 7451.366 MPa. from the results of the study it can be concluded that the addition of fly ash with a variation of 10% is still able to increase the compressive strength, split tensile strength and elastic modulus. However, the addition of more than 8% marble ash can reduce the value of compressive strength, split tensile strength and modulus of elasticity.